An evaluation of domestic electric water heaters for frequency control - Xiang, Sheng; Yang, Hongming; Cao, Bo (Frontiers in Energy Research, 2022)
Maintaining the frequency of a power system close to its nominal value (50 Hz or 60 Hz) is critical, which comes mainly from generators and flexible loads in traditional power systems. Direct load control (DLC) is a method to control controllable loads for power system optimization, generally, it is used to reduce or shave peak demand. Nevertheless, DLC also can be used to provide frequency control services. Domestic electric water heater (DEWH) is an important kind of controllable load, which takes a high percentage of domestic electric power consumption and has a large thermal energy storage capacity. Hence, DEWH can be a prime candidate for DLC. This paper proposes a framework to provide frequency control service with DEWHs. A virtual battery pack system (VBPS) is introduced to equivalent the capacity of DEWHs, and a series of measurable indicators are proposed to show the capacity of the VBPS when providing frequency control services. An adaptive criterion is employed to classify controllable DEWHs, which helps to maintain end-user comfort. The performances of the proposed frequency control method during normal and contingency conditions are verified through case studies in CYME.